THE EFFECT OF FEEDING RULES ON THE NUTRITIONAL STATUS OF TODDLERS AGED 24-59 MONTHS IN THE WORKING AREA OF THE TAWANGHARJO COMMUNITY HEALTH CENTER, GROBOGAN REGENCY. - Dewi Sapta Wati; Wahyu Utami Ekasari (Jurnal Profesi Bidan Indonesia, 2025)
Background: Feeding rules are guidelines for feeding that include schedules, types, portions, and parental responsiveness in feeding toddlers. Mothers' knowledge of feeding rules plays an important role in shaping toddlers' eating patterns and nutritional status. Objective: To analyze the effect of knowledge of feeding rules on the nutritional status of toddlers aged 24–59 months. Methods: This was a quantitative analytical cross-sectional study involving 97 mothers of toddlers. Knowledge of feeding rules was categorized as adequate in 38 (39.2%) respondents, good in 36 (37.1%) respondents, and poor in 23 (23.7%) respondents. The nutritional status of toddlers was measured using the weight-for-age indicator based on WHO standards. Bivariate analysis used Somers' d test to determine the direction and strength of the relationship between ordinal variables. Results: The majority of feeding rules knowledge was in the adequate category (39.2%), while the nutritional status of toddlers was dominated by good nutrition (64.9%). Somers' d test showed a significant relationship between knowledge of feeding rules and nutritional status (d = 0.462; p = 0.001). The positive direction of the relationship indicates that the better the knowledge of feeding rules, the better the nutritional status of toddlers.Conclusion: Knowledge of feeding rules has a significant effect on the nutritional status of toddlers. Improving education on feeding rules can be an effective strategy for preventing nutritional problems in toddlers.